Experimental models for vascular endothelial dysfunction (Bangladesh Journal of Pharmacology, 2021)
Vascular endothelial dysfunction is characterized by apoptosis of endothelial cells, an imbalance between vasoconstrictory and vasodilatory substances, the imbalance between ROS and antioxidants, vascular remodeling, loss of vascular integrity which leads to an increased risk of cardiovascular complications. To date, no therapeutic intervention is available as a promising agent. This may be due to a poor understanding of the underlying mechanism involved in vascular endothelial dysfunction in the pathogenesis. Animal models sharing identical features as that of humans are paramount to understand fundamental physiology, mechanism and to explore new targets for developing therapeutic agents. Thus, it becomes mandatory to re-explore the available animal models for a better understanding of molecular pathways involving vascular endothelial dysfunction. The purpose of this paper is to review different models for vascular endothelial dysfunction to the outlook for developing new drugs to treat vascular endothelial dysfunction.